Compendium of British Office Holders - Venning, Timothy. author. aut Link
XXIV, 696 p.
Keywords: The Compendium of British Office Holders provides a comprehensive guide to holders of British Political, Administrative, Military and Ecclesiastical offices since the Roman conquest, giving names, dates and the length offices were held for governmental positions. It is the first such collection of this type of research data since Haydn's Dictionary of Dates was published back in 1894 and will provide the reader with quick and easy access to specific factual information for research.